Malaysian model of entrepreneurship development for its indigenous people / Mohammad Saeed and Kamal Kishore Jain - Saeed, Mohammad; Jain, Kamal Kishore (Faculty of Business and Management ; UiTM Press, 2000)
As a traditional trading nation, Malaysians have been endowed with different types of entrepreneurial skills. The entrepreneurs in Malaysia have so far been fortunate with the favorable economic climate and the Government's strong commitment to provide a conducive environment for entrepreneurs. This paper examines the Government policies and the support system that exist in Malaysia to promote entrepreneurial efforts among its indigeneous people.